Diffusion of organic farming among Dutch pig farmers: An agent-based model. (March 2022) - Ambrosius, Floor H.W.; Kramer, Mark R.; Spiegel, Alisa; Bokkers, Eddie A.M.; Bock, Bettina B.; Hofstede, Gert Jan
Abstract: CONTEXT: Organic farming is an alternative for conventional farming practices with the potential to decrease negative externalities. Yet, in the Netherlands there has been a mismatch between societal preferences and farmer behaviour: despite increasing demand for organic pork meat, farmers feel peer pressure to remain conventional. Therefore, to understand diffusion of organic farming, one needs to consider social dynamics between farmers. OBJECTIVE: The aim of this research is to gain insight in the factors contributing to the diffusion of organic farming, by considering social interaction mechanisms, market price dynamics, and heterogeneity in farming styles. METHODS: We built an agent-based model of pig farmers differing in farm size and farming style (idealists, craftsmen and entrepreneurs) in a social-spatial network. They can convert from conventional to organic farming and back. Farmers can influence one another when they interact. This social influence is based on the social identity approach: Farmers who are similar in, among others, farming style converge in attitudes, while dissimilar farmers diverge in attitudes. The conventional meat price is volatile. The organic meat price fluctuates in accordance with supply. An exploratory analysis was performed on social influence parameters. Three social influence scenarios on the likelihood for influence in interaction were selected for local sensitivity analysis. The model run replicated 15 years and started with 16 organic farmers and 1958 conventional farmers. Model results were discussed with Dutch organic pork sector experts. RESULTS AND CONCLUSION: The results of the exploratory analysis are threefold. An increase in the likelihood of influence in interaction increases the number of organic farmers from 44 to 121 and diversifies the organic farmers from 98% idealists to 31% idealists, 49% craftsmen and 20% entrepreneurs. The most influential factor on diffusion of organic farming is the demand for organic pork meat. New entrants stimulate organic farming through a different farming style than their predecessor. Expert discussion on model results confirmed the importance of consumer demand and new entrants for understanding diffusion. SIGNIFICANCE: The social identity approach serves as a helpful framework to capture empirical and sociological knowledge. It reveals that farming styles of entrants contribute to the diversification of farming practices overall. For researchers and policy makers wishing to stimulate alternative farming practices, it is of interest to better understand this mechanism. In addition, we showed that those wishing to understand innovation in farming practices should look beyond farmer decision-making, by including market dynamics through consumer demand. Graphical abstract: Unlabelled Image Highlights: Understanding diffusion of organic farming requires a systems approach Trend in consumer demand can stimulate or limit diffusion of organic farming New entrants influence diffusion of organic farming through their farming style and their peers Local interactions can influence diversification of farming styles among organic farmers